HARDINESS PERSONALITY AND ASSOCIATED FACTORS IN PROFESSORS OF UNDERGRADUATE HEALTH COURSES. - de Oliveira Nascimento Alves, Ana Paula; Junior, Rene Ferreira da Silva; Santos, Lara Isabella Souza; Siqueira, Leila das Graças; de Oliveira e. Silva, Carla Silvana; Dias, Ana Catarina Perez (Revista de Pesquisa: Cuidado é Fundamental)
Objective: to identify the factors associated with the hardiness personality among professors working in higher education at a federal institution. Method: epidemiological, cross-sectional and analytical study with 88 professors from undergraduate health courses in the institution. The hardiness scale associated with a questionnaire was used to investigate sociodemographic and occupational characteristics. Results: Moderate to high hardiness was found among the professors and this personality was associated with variables such as having children, having taken vacations in the last year, not having used prescription drugs in the last year and not having a diagnosis of anxiety disorder, that is, they exhibited resilience patterns related to a condition of coping with stress. Conclusion: teachers who displayed occupational resistance had important protective factors for their health, in addition, they collaborated to make the work environment more harmonious, which could favor the teaching-learning process.